Analysis Of General Business Behavior In Implementing Marketing Mathematics In The Digital Era - Sabariah, Etika; Hartanti, Hartanti; Suprianto, Agung (Sean Institute, 2025)
This study explores business behavior in applying marketing mathematics in the context of conventional and online businesses. The main distinction between these types of businesses lies in their promotional strategies, packaging adjustments, and methods of identifying customer numbers. This applied qualitative research employs observational data on business behavior and literature studies to support deductive reasoning for formulating decision-making theories. The analysis reveals the influence of business behavior in applying marketing mathematics, including: (1) identifying customer needs in conventional and online contexts, (2) utilizing graphs for decision-making, (3) adjusting packaging sizes to meet consumer needs, and (4) synchronizing marketing and production mathematics. Accurate estimations in this synchronization process significantly impact work instructions. These instructions detail real-time steps in the marketing phase, which subsequently guide production. This ensures minimal discrepancies between inventory inflows (production) and outflows (sales), reducing stockpiling and optimizing working capital, particularly for food and beverage entrepreneurs. Unlike artificial intelligence (AI), effective work instructions remain a critical business strategy, incorporating Strengths, Weaknesses, Opportunities, and Threats analysis across divisions. The unique interrelation between production and marketing divisions highlights the irreplaceable human element in crafting responsive strategies, making this process essential for achieving business efficiency and reducing operational waste.